Implementation of the Sustainable Food Garden Program (P2L) as an Effort to Accelerate the Reduction of Stunting In Bone Regency - Anisa Fitri; Moh Thahir Haning; Suryadi Lambali (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
This study aims to determine the implementation of a sustainable food garden program as an effort to accelerate the reduction of stunting in Bone Regency. The research method used is descriptive qualitative research. This study focuses on policy implementation using Merilee S Grindle's theory. The data analysis technique used is the Miles and Huberman model, namely data reduction, data presentation, and drawing conclusions. The results showed that the implementation of sustainable food garden program as an effort to accelerate the reduction of stunting in Bone Regency has been going well, in accordance with Merilee S Grindle's implementation theory. With several sub-indicators, the contents of the policy are interests, benefits, changes, decision-making, and program implementers. While the indicators that need to be improved are resources. Resources need to be increased so that the provision of vegetable seeds to the community can be more evenly distributed